2011
DOI: 10.1007/s00210-011-0680-4
|View full text |Cite
|
Sign up to set email alerts
|

Rat intermedin1-47 does not improve functional recovery in postischemic hearts

Abstract: Intermedin, a novel member of the calcitonin/calcitonin gene-related peptide family identified from vertebrate genomes, may directly affect cardiac function but current studies revealed no clear picture. The aims of our study were to compare direct contractile effects of intermedin on cardiomyocytes to that on the whole organ and to investigate whether intermedin improves postischemic recovery independent of an effect on acute reperfusion injury. Isolated adult rat ventricular cardiomyocytes were electrically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…In our study, myocardial NOS activity and NO were significantly decreased in both nondiabetic and diabetic animals after MI/R. Previously, intermedin has been shown to exert negative inotropic effects in Langendorff-perfused rat hearts, an effect blocked by inhibition of nitric oxide synthesis [57]. Another study demonstrated IMD increased endothelial nitric oxide synthase (eNOS) phosphorylation nearly three-fold at Ser (1177), significantly enhancing eNOS activity [58].…”
Section: Discussionsupporting
confidence: 48%
“…In our study, myocardial NOS activity and NO were significantly decreased in both nondiabetic and diabetic animals after MI/R. Previously, intermedin has been shown to exert negative inotropic effects in Langendorff-perfused rat hearts, an effect blocked by inhibition of nitric oxide synthesis [57]. Another study demonstrated IMD increased endothelial nitric oxide synthase (eNOS) phosphorylation nearly three-fold at Ser (1177), significantly enhancing eNOS activity [58].…”
Section: Discussionsupporting
confidence: 48%
“…This contradiction may be due to the contribution of NO. In cultures of cardiomyocytes, ADM2/IMD 1–47 has a positive inotropic effect through the cAMP‐Ca 2+ pathway, but in isolated hearts, ADM2/IMD 1–47 has an opposite effect in an NO‐dependent manner (Munzel et al , ). The negative inotropic effect of ADM2/IMD 1–47 depends on the endothelium through the CGRP/AM 1/2 receptor‐eNOS‐cGMP pathway.…”
Section: Cardiovascular Effects Of Adm2mentioning
confidence: 99%
“…vasodilator, vasodepressor) (Takei et al 2004) and in the heart both were shown to modulate myocardial function Fontes-Sousa et al 2009;Pires et al 2012). However, in contrast to the normal heart where its action has been comprehensively studied (Roh et al 2004;Takei et al 2004;Munzel et al 2011;Pires et al 2012) the myocardial effects of IMD in the diseased heart remain unexplored. With this in mind, we investigated in the present study the myocardial action of IMD 1−47 and the underlying mechanisms in well-known rat models of left ventricular (LV) hypertrophy due to pressure overload (transverse aortic constriction, TAC) or nitric oxide (NO) deficiency associated with chronic NO synthase inhibition…”
Section: Introductionmentioning
confidence: 99%